The development and characterization of a novel coagulant for dust suppression in open-cast coal mines - Gang Zhou; Tao Fan; Mao Xu; Han Qiu; Jiayuan Wang; Lei Qiu (Adsorption Science & Technology, 2018)
This paper proposes the development of a novel coagulant for dust suppression in open-cast mines. Specifically, pretreated sodium lignin sulfonate and acrylic acid were first cross-linked, then the graft copolymerization of the intermediate product (the cross-linking product) and acrylamide was conducted and finally the resulting gelatinous substances were crushed. During the reaction process, N,N’-methylene-bis-acrylamide and ammonium persulfate were used as the cross-linking agent and initiator, respectively. Subsequently, the functional groups, crystalline structure, and thermal stability of the dust coagulant were examined by means of Fourier transform infrared spectra measurements, X-ray diffraction spectra measurements, and differential scanning calorimeter analysis. Moreover, single-factor experiments were conducted to explore the optimal synthesis condition. According to the experimental results, the coagulant achieved its optimal dust suppression performance under the following conditions: the mass ratio of lignin to acrylic acid was 1:3, the mass ratio of lignin to acrylamide was 2:7, the content of the cross-linking agent was 0.9%, the mass ratio of initiator to acrylamide was 2:100, the reaction temperature was set as 60℃, and the pH value was set as 7. Finally, the coagulant was measured for its swelling kinetics, viscosity, film-forming hardness, peeling strength, and ability to suppress dust. It can be concluded that the coagulant exhibits a very high standard of both dust suppression and wind resistance.